Use of World Health Organization susceptibility test for malaria vector control in South-Eastern Nigeria: A discourse - Joel D Akilah; Ibanga Eyo Ekong (Wolters Kluwer Medknow Publications, 2019)
Background: With growing evidence of mosquito vector resistance to pyrethroids and other classes of insecticides globally, we employed one of the two important tools for the monitoring of insecticide resistance in selected states in southeastern part of Nigeria via the World Health Organization (WHO) susceptibility test. Aim: This study tested the effectiveness of WHO susceptibility test for the use in identifying and monitoring the resistance of Anopheles and Aedes mosquitoes which transmit malaria and arbovirus-related diseases in Nigeria. Methods: Larval sampling of mosquitoes was embarked upon with ovitraps set in various study sites; eggs were hatched and reared and subsequently subjected to susceptibility tests according to the WHO test procedures. Summary and Conclusion: Resistance to dichloro diphenyl trichloroethane and the pyrethroids has been established to a large extent. The loss of efficacy of pyrethroids may result in operational failure of disease control programs.